Effect of shear wall on seismic performance of RC frame buildings - Ozkul, Tulay Aksu; Kurtbeyoglu, Ahmet; Borekci, Muzaffer; Zengin, Basak; Kocak, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Buildings can have heavy damages or collapse because of severe earthquakes. Previous studies showed that structural damage due to earthquake is the cause of large displacement. Shear walls in the buildings ensure safety against lateral loads. Thus, using shear walls in buildings can be prevent large displacement and herewith damages due to displacement. The last devastating earthquake is Van 2011 earthquake in Turkey and many buildings were damaged because of Van 2011 earthquake. There were buildings which have shear walls among those damaged buildings. However, it is clear not only shear walls but also whole building should be designed according to a modern seismic code. In this study, two RC buildings with shear walls which had damages because of Van 2011 earthquake were considered and it is tried to determine the existing damages via nonlinear time history analysis using Van 2011 earthquake acceleration data. Time history analyses were conducted with SAP 2000. In addition to this, material qualities were increased and shear walls were designed according to Turkish Seismic Code 2007 requirements for both buildings. Nonlinear time history analyses were conducted for the upgraded buildings and damage distributions were determined. Thus, damage distributions of existing and upgraded buildings were compared and an evaluation was drawn for damage distribution even if only proper concrete and reinforced material and shear walls were used in design of the buildings except beams and columns. According to results of the study, using proper materials and shear walls can prevent heavy damages even seismic response of beams and columns elements is poor.
Keywords: Earthquake damage; RC buildings; Shear walls; Nonlinear time history analysis; STRUCTURAL WALLS; Engineering; Materials Science